Analysis of counselor task commitment as a professional characteristic in junior and senior high schools in West Sumatra - Tas'adi, Rafsel; Ardimen, Ardimen; Hadiarni, Hadiarni; Tanjung, Romi Fajar (Jurnal Konseling dan Pendidikan, 2024)
Task commitment is an important thing for counselors to have so that the counseling profession provides professional services to various stakeholders. This research aims to look at the job commitment profile of middle school and high school level counselors so that it can be used as an evaluation regarding the counselor's current performance or services. The population in this study were counselors in eight cities in West Sumatra. This study uses a quantitative approach. The research sample was determined using an accidental sampling technique (convenience sampling), namely the sampling process simply involves taking the counselors the observer meets in the field. The research sample obtained was 86 counselors. The data collection technique was carried out by distributing questionnaires. The collected data was analyzed quantitatively using the SPSS 25 for Windows program and the Excel application for processing quantitative descriptive analysis, categorization and percentages and producing graphical data. The research results show that the majority of counselors' task commitment is in the very high category for all indicators, namely tough attitude, tenacity, not getting bored easily, independence, courage to take risks, desire to improve themselves, and desire to succeed.